The Fate and Effects of Crude Oil Spilled on Subarctic Permafrost Terrain in Interior Alaska - Johnson,Larry A; Collins,Charles M; Sparrow,Elena B; Jenkins,Thomas F; Davenport,Charlotte V (1980)
This study was conducted to determine the short- and long-term physical, chemical and biological effects of spills of hot Prudhoe Bay crude oil on permafrost terrain near Fairbanks, Alaska. Two experimental oil spills, one in winter and one in summer, of 7570 liters (2000 gallons) were made at a forest site. The winter-spill oil moved within the surface moss layer beneath the snow. The summer-spill oil moved primarily below the moss in the organic soil. The oil moved faster and further downslope in the summer spill. Oil in the winter spill stopped during the first day but remobilized and flowed further downslope in the spring. The total area affected by the summer spill was nearly one and one-half times as large as that affected by the winter spill. The initial heat of the spilled oil had little measurable thermal effect on the soil. However, thaw depth significantly increased following two full thaw seasons. The greatest increases occurred beneath oil blackened surfaces. Evaporation of volatile components is the most significant weathering process in the first two years. Volatiles evaporated faster from surface oil than from oil carried deeper into the soil profile. Microbial degradation has not been observed. The indigenous soil microbial populations responded differently to winter and summer oil applications, ranging from inhibition to stimulation, with stimulation appearing to predominate. Vegetation showed both immediate and long-term damage. Damage was greatest near the top of the slope and in areas with surface oil. Deciduous species showed damage faster than evergreen species. (Author)